Penggunaan Metode Algoritma Craft dan Blocplan untuk Perbaikan Tata Letak Fasilitas Lantai Produksi pada Industri Sparepart Sepeda Motor - Leonardo Leonardo; Hotma Antoni Hutahaean (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
Performance and productivity of production line system are very influenced by facility layout planning.Facilities composition which is appropriate with flow of materials between departments, certainly wouldsustain the continuity of the system. PT. X is one of the subsidiaries of PT. Astra Otoparts Tbk. whichmanufactures motorcycle chains. Composition of the current layout facilities on the 1st Plant has not fullyoptimized well and indeed has a potential possibility to be developed further in the future. This statement issupported from the result of existing MHPS which gives Rp 1,047,678.49 for total cost of material handling,463.1 meters for total distance, and 1,617.24 minutes for total time of material movements. Also, the totalarea of empty spaces that can be utilized by the company in the current layout is only 89.74 m2. As for thepurposes of this research are: analyzing the performance of current layout, developing new layout designs toimprove the current one, and comparing the current with proposed improvement layouts. The process ofdesigning proposed layouts is done by using improvement-based algorithm (CRAFT) and hybrid/compositealgorithm (BLOCPLAN) that both of the algorithms need same inputs, which are: current facility layout andthe flow of material. Based from the results of MHPS calculation for both proposed layouts, show that layoutfrom BLOCPLAN algorithm gives maximal reduction to the total cost of material handling so that theamounts will be decreased to Rp 1,022,419.91 (reducing 2.4% from total cost of current layout), 434.62meters for total distance (reducing 6.2%), and 1,506.23 minutes for total time of material movements(reducing 6.86%). As for the total area of empty spaces, BLOCPLAN layout gives 110.74 m2 (23.4%) to beminimized than the current layout.